Uji Daya Hambat Ekstrak Rumput Laut (Eucheuma cottonii) Terhadap Pertumbuhan Bakteri Staphylococcus aureus - inaya, Fidjrina rahma; A.R. Pratiwi Hasanuddin; Aryandi, Rahmat (Jurnal TLM Blood Smear, 2023)
Staphylococcus aureus is a gram-positive bacterial pathogen that looks like grapes. Staphylococcus aureus can cause skin infections (boils, impetigo, furuncles, wound infections, staphyloccus scalded skin syndrome). Each plant produces chemical compounds produced by the plant itself (Fatimah et al., 2016). The plant in question is seaweed (Eucheuma cottonii) which contains nutrients such as polysaccharides and fiber which have antibiotic, anticoagulant, anticancer, antipriloferatif (anti-uncontrolled cell division), antiviral and anti-inflammatory (anti-inflammatory) activities. has antibacterial activity, which can be used as an antibiotic. Research objectives, the purpose of this study was to determine whether seaweed extract could inhibit the growth of Staphylococcus aureus bacteria. Research methods, The research method used is the disc diffusion method. The data were statistically tested using the Kruskal-Wallis test, the treatment group in this study consisted of a positive control of chloram phenicol, a negative control of sterile distilled water and a concentration group of 100%, 80%, 60%, 40%, and 20% with 3 repetitions for each group. Conclusion, It can be concluded that Seaweed Extract (Eucheuma cottonii) has an inhibitory power against the growth of Staphylococcus aureus in the weak category.